PENGARUH ENVIRONMENT & FACILITIES, WAITING TIME, DOCTOR-PATIENT COMMUNICATION, DAN PROFESSIONAL SERVICE TERHADAP OVERALL SATISFACTION MELALUI AKSES INFORMASI PENGOBATAN PADA PASIEN RAWAT JALAN NON BPJS DI RS XYZ MANADO - Sorongan, Christian Hendrikus; Oliandes Sondakh, (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This research aims to analyze the effects of environment & facilities, waiting time, doctor-patient communication, and professional service on theoverall satisfaction of outpatient patients at Manado XYZ Hospital, with accessibility for treatment information as a mediating variable. The background of this research is based on the importance of patient satisfaction as an indicator of healthcare service quality, which is influenced by the patient experience during the care process. Using a quantitative approach, quantitative data were obtained through an online- distributed questionnaire, employing a cross-sectional method. The questionnaire was modified based on questions found in previous literature. This study involved 100 respondents who were analyzed using the Structural Equation Modeling (SEM) method with a Partial Least Square (PLS) approach.The results of this study show that Accessibility for Treatment Information has a positive and significant impact on patient satisfaction, indicatingthe importance of transparency of information in healthcare services.